PENGARUH KOMPETENSI KARYAWAN, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI LPD KOTA DENPASAR - Febriyani, Ni Putu; Sari Widhiyani, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024, 2024)
The information system used by financial institutions is an accounting information system. The performance of the accounting information system is very important to evaluate because it can provide an overview of whether the performance of the available system is in accordance with what is needed and the goals of the company or organization. The purpose of this research is to empirically prove the effect of employee competence, work motivation, and organizational culture on the performance of accounting information systems. The population of this research are included 34 LPDs throughout Denpasar City. The sampling method uses purposive sampling technique where three respondents were selected for each LPD, which is the head of the LPD, the accounting department, and the credit department so that 102 employees were obtained as respondents. The analytical tool used is SPSS with data analysis techniques namely multiple linear regression analysis. The results of the analysis show that employee competence, work motivation, and the organizational culture have a positive effect on accounting information system. The increase in employee competence, increase in work motivation, and the better the organizational culture will also increase the performance of the accounting information system too.